Halide-free deep eutectic solvents constructed from natural compounds for converting carbon dioxide to cyclic carbonate - Yu, Wen-Wang; Meng, Xiang-Guang; Li, Wen; Zhou, Jie; Ma, Xian-Jian; Chu, Dan-Dan (Chemical communications (Cambridge, England), 2025)
Halide-free deep eutectic solvents (DESs) derived from natural biological compounds were used to gently catalyze the cycloaddition reaction between CO 2 and epoxides, with a TOF of 645 h −1 . The DFT calculation result was in good agreement with the experiment result, indicating that the ring closure process was the rate-determining step. Halide-free deep eutectic solvents (DESs) constructed from natural compounds were used to efficiently transform CO 2 into cyclic carbonates.